2013
DOI: 10.1111/jre.12091
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke inhalation increases the alveolar bone loss caused by primary occlusal trauma in a rat model

Abstract: Short-term CSI increases early bone loss in association with OT after 7 d, and this worsens in severity after 14 d of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…There are many local contributing factors that accelerate the bone loss process, such as dental calculus, bacterial factors, and occlusal trauma. Occlusal trauma is defined as an injury to the periodontium caused by traumatic force that exceeds the reparative capacity of periodontal tissues . It has been suggested that occlusal trauma may result from questionable restoration; bruxism or clenching that alters the force applied to teeth.…”
Section: Introductionmentioning
confidence: 99%
“…There are many local contributing factors that accelerate the bone loss process, such as dental calculus, bacterial factors, and occlusal trauma. Occlusal trauma is defined as an injury to the periodontium caused by traumatic force that exceeds the reparative capacity of periodontal tissues . It has been suggested that occlusal trauma may result from questionable restoration; bruxism or clenching that alters the force applied to teeth.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that there is alveolar bone loss in occlusal trauma 1,8,15 , because all periodontal support tissues are involved. However, there is no information in the literature about the type of occlusal condition and its pathogenic intensity in the periodontium.…”
Section: Discussionmentioning
confidence: 99%
“…Due to ethical limitations on prospective evaluation of OT in humans, 2 experimental models in rats were developed for the present study, with the goal of evaluating the consequence of the type of occlusion on the development of bone loss in primary OT. In one of the models, occlusal interference 7,8,11 was created to imitate experimentally the occlusal interferences and premature occlusal contacts that lead to the increase in the vertical dimension of occlusion, leading to occlusal instability by altering the force vectors and changing the magnitude of the applied forces to one tooth. In the other model, the unilateral vertical dimension was reduced, creating occlusion on only one of the first molars, with the goal of reproducing experimentally the cases of partial edentulism 15 , also creating occlusal overload experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations